Case Report: Challenges in diagnosing Kawasaki disease in children under 3 months of age: a case series report - Phi, Duc Long; Nguyen, Thi Hoai; Duong, Khanh Linh; Nguyen Le, Cam Anh; Nguyen, Duy Cuong; Hoang, Van Thuan (Frontiers in Pediatrics, 2025)
Infants younger than 3 months old often present with incomplete Kawasaki Disease (KD), where not all the classical features are present. This makes the diagnosis challenging, as KD may be easily confused with other common pediatric conditions, such as viral infections, bacterial sepsis, or toxic shock syndrome. Moreover, the risk of developing coronary artery abnormalities is reportedly higher in younger infants, making timely diagnosis and treatment critical. Here we reported three cases of KD in infants under three months, each illustrating the challenges in diagnosis due to the absence of typical KD symptoms such as rash, conjunctivitis, and oral mucosal changes. Echocardiography played a pivotal role in identifying coronary artery abnormalities, leading to the diagnosis of incomplete KD in all cases. Clinicians should maintain a high index of suspicion for KD in any febrile infant, particularly when inflammatory markers are elevated. Early recognition and treatment are vital to prevent severe cardiovascular complications.